CREATING AND USING VIDEO CONTENT BASED ON PARABLES OF YBYRAIALTYNSARIN AS A MEANS OF ACHIEVING EDUCATIONAL PURPOSE - Важницына, А.С.; Циммерман, Д.Е. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
We know about the enlightening activity of Y.Altynsarin, about his works and what things they teach. But we don’t really pay much attention to how they are important to modern teachers and students. We hold a lesson of Kazakh History and English in Team-Teaching form where we showed practical appliance of works of the great enlightener. A short videoclip devoted to the pаrable “A Father and a Son” was made as a means of demonstration. By means of the parable students were engaged in listening, speaking, it could also educate spiritual, patriotic values to students. Moreover it implements objectives of the national idea of Trilinguism. Judging by this, we came to the conclusion that pedagogical ideas of Ybyrai Altynsarin are actual at the lessons of both junior and senior students.
Keywords: Educator; education; spiritual and moral upbringing; parables; essence; IT forms